Horsmanship and warriors in the burial customs of the Early Iron Age in Southeastern Europe. A case study - Potrebica, Hrvoje (Array, 2001)
Southeastern Europe is a contact area between Mediterranean civilisations and cultural complexes of the Central Europe. The nature of that relationship was often seen as one-dimensional, or in an oversimplified way. The research in last few decades indicates that the cultural communication over this area was far more complex and dynamic than it was ever thought. In order to understand these intricate phenomena, we have to establish certain chronological relations between them. There are almost no absolute dates for the Early Iron Age of this area. Since the central European chronological scheme is conceptually unacceptable in this area, all we have are regional relative chronologies based on typological analysis. Such chronologies depend much on &#8220 ; the point of view&#8221 ; , that is on the area and corpus of finds the creator of such chronology is primarily working on. The accuracy of those chronologies rapidly falls with the distance from the core area. The another solutions are local relative chronologies that function perfectly within certain cultural groups, but in most of the cases, cannot be applied to another cultural phenomenon. They are also hard to synchronise with similar chronologies in a broader area of research. The most objective way to establish chronology of cultural changes would be to establish actual changes in the way of life that are usually reflected in well documented settlement stratigraphy. Unfortunately, only a couple of such sites have been excavated so far. The only closed archaeological units that are relevant for chronological discussion, thus remain graves. Since the warriors are the most distinctive, and in partially the determinative element of the Early Iron Age as different stage of cultural development, we should take them in the focus of any such analysis. The analysis of changes of the warrior concept, especially in the appearance and evolution of horsemanship element, reflected in burial customs and grave inventories in this large and coherent area, reveals subtle and intricate scheme of cultural interrelations and influences that left deep traces on both centres of cultural development. Through the study of some special categories of burial customs (such as the appearance of wagon burials), as well as special groups of items within grave inventories (such as sets of defence weapons and horse gear), this paper will try to give an overview of general chronological markers as well as direction of cultural changes marked by the long trade routes of prestigious objects.